The Effect of Cardiopulmonary Bypass Surgery on Arginase Activity and Nitric Oxide Levels - Dogan, Ayse; Ozan, Sema Temizer; Kısaçam, Mehmet Ali; Kocamüftüoğlu, Gonca Ozan; Turker, Fevzı Sarper (My University, 2018)
Objective: The aim of the study was to assess the endothelial function with arginase activity and nitric oxide (NO) levels in patients undergoing coronary artery bypass grafting (CABG) surgery.Materials and Methods: The study was conducted on 26 patients undergoing CABG surgery. Blood samples were collected from the patients in the preoperative, peroperative, and postoperative periods. Arginase activity and NO levels were measured spectrophotometrically from the collected samples.Results: Arginase activity decreased significantly in patients in the peroperative period compared to the preoperative period. There was no significance in terms of arginase activity in the postoperative period compared to the preoperative and peroperative periods. On the other hand, NO levels increased significantly in patients in the peroperative period. There was no significant increase in terms of NO level in the postoperative period; whereas, there was an insignificant increase compared to the preoperative period.Conclusion: Complications that may occur after the bypass surgery can be avoided by determining the treatment methods that will prevent the decrease in NO level and the increase in arginase enzyme activity occurring as a result of the bypass surgery and it can be ensured these patients to have a more enhanced quality of life and to be healthy after the surgery.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Kalp ve Kalp Damar Sistemi